Relevansi Yurisprudensi Mahkamah Agung RI No.1506 K/Pdt/2002 dalam Transaksi Bisnis Internasional - Denny Tendra (UNES Law Review, 2023)
In international business transactions carried out by Indonesian business actors, both on an UMKM and large scale, with foreign business actors, there are those who do not make anchor agreements regarding the sales and purchases they make, and only use purchase orders and the sender's email as their sales and purchase agreements. However, when a dispute arises and is tried in an Indonesian court regarding a purchase order, this has different meanings and interpretations by legal and economic experts, so a uniform interpretation of purchase orders is needed that has legal certainty. In this regard, there is legal certainty regarding the purchase order, namely the Supreme Court jurisprudence No.1506 K/Pdt/2022. This jurisprudence can be used by parties in protecting international sales and purchases that are tried in Indonesian courts.